Adaptive Immune Responses Contribute to Post-ischemic Cardiac Remodeling - Santos-Zas, Icia; Lemarié, Jérémie; Tedgui, Alain; Ait-Oufella, Hafid (Frontiers in Cardiovascular Medicine, 2019)
Myocardial infarction (MI) is a common condition responsible for mortality and morbidity related to ischemic heart failure. A large body of experimental and translational evidence support a major role for innate immunity in heart failure and adverse heart remodeling following MI. More recently, the role of adaptive immunity in myocardial ischemia has been identified, mainly in rodents models of both transient and permanent heart ischemia. The present review summarizes the accumulating experimental evidence regarding the role of lymphocytes and dendritic cells in myocardial remodeling following coronary artery occlusion. Th1 and potentially Th17 CD4+ T cell responses promote adverse heart remodeling, whereas regulatory T cells appear to be protective, modulating macrophage activity, cardiomyocyte survival and fibroblast phenotype. The role of CD8+ T cells in this setting remains unknown. B cells contribute to adverse cardiac remodeling through the modulation of monocyte trafficking, and potentially the production of tissue-specific antibodies. Yet, further substantial efforts are still required to confirm experimental data in human MI before developing new therapeutic strategies targeting the adaptive immune system in ischemic cardiac diseases.